PUBLIC RELATION STRATEGY OF PT. NATURAL NUSANTARA (NASA) IN BUILDING BRAND AWARENESS - Fais, Ainur; Tasrif, Muh (QAULAN: Journal of Islamic Communication, 2022)
Abstract: The research method in this study using qualitative research approach with descriptive analysis. Data collection using interview and documentation. Data analysis technique using Ronald D. Smith’s theory that’s strategic planning for public relations with four stages of branding awareness: formative research, strategy, tactics, and evaluative research. The result of the study is (1) PT. Natural Nusantara is a company that using multi level marketing business system. NASA’s strategy to introducing his products to consumers throught to seminars and training for the members about new product that has been launched. Market analysis, planning and and strategy, tactic of communication also evaluation from the event arranged by the company. (2) A supporting factor in building NASA's brand awareness is the presence of technicians or consultants from each field in the product category who are really qualified, and the obstacle factor is the information system and NASA’s business system can’t entering to the digital platform specifically marketplace because it is prohibited by the Ministry of Trade.